Question

sol. (3) Expression
( =frac{frac{3}{15} a^{5} b^{6} c^{3} times frac{5}{9} a b^{5} c^{4}}{frac{10}{27} a^{2} b c^{3}} )
( =left(frac{3}{15} times frac{5}{9} times frac{27}{10}right)left(frac{a^{6} b^{11} c^{7}}{a^{2} b c^{3}}right) )
( frac{3}{10} a^{6-2} b^{11-1} c^{7-3} )
( =frac{3}{10} a^{4} b^{10} c^{4} quadleft[begin{array}{l}because a^{m} times a^{n}=a^{m+n} a^{m}+a^{n}=a^{m-n}end{array}right] )

# Ex.4. The simplified value of following is (* ಹಿತಿ b) a°be (9) Sa+b (10 (3) _10 4 ) 10

Solution